1989
DOI: 10.1029/wr025i012p02521
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “A note on the recent natural gradient tracer test at the Borden site” by R. L. Naff, T.‐C. Jim Yeh, and M.W. Kemblowski

Abstract: The tracer test at the Borden Site [Mackay et al., 1986;Sudicky, 1986;Freyberg, 1986] has generated considerable interest, being one of the first field experiments in which both concentration distributions and formation properties have been measured extensively. A few attempts have been made in the past in order to compare field measurements with existing theoretical formulae which relate the concentratio½ to aquifer heterogeneity.The author's [Naff et al., 1988] main thesis is that the measured particles dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Early research at Borden, and at the other field sites with concentrated research programs such as Cape Cod and the Columbus AFB, did not include delineating and quantitatively representing lithologic unit types. The early articles discussing dispersion at the Borden site contained speculation about the presence of lenses or layers of different strata [e.g., Dagan, 1989aDagan, , 1989bNaff et al, 1988Naff et al, , 1989Woodbury and Sudicky, 1991;Rajaram and Gelhar, 1991], signaling posterior recognition of the importance of knowing the sedimentary architecture in order to explain transport processes. Given that the sedimentary architecture of Borden site, with relatively mild contrast in Y between unit types, controls conservative solute spreading [Ramanathan et al, 2010], then the architecture at other sites with higher Y contrasts between units likely does also.…”
Section: Discussionmentioning
confidence: 99%
“…Early research at Borden, and at the other field sites with concentrated research programs such as Cape Cod and the Columbus AFB, did not include delineating and quantitatively representing lithologic unit types. The early articles discussing dispersion at the Borden site contained speculation about the presence of lenses or layers of different strata [e.g., Dagan, 1989aDagan, , 1989bNaff et al, 1988Naff et al, , 1989Woodbury and Sudicky, 1991;Rajaram and Gelhar, 1991], signaling posterior recognition of the importance of knowing the sedimentary architecture in order to explain transport processes. Given that the sedimentary architecture of Borden site, with relatively mild contrast in Y between unit types, controls conservative solute spreading [Ramanathan et al, 2010], then the architecture at other sites with higher Y contrasts between units likely does also.…”
Section: Discussionmentioning
confidence: 99%
“…The nonlinear variogram fitting procedure also revealed that considerable uncertainty can exist in the values of the geostatistical parameters, which, in turn, will lead to uncertainty in the values of effective, large‐scale transport parameters predicted by stochastic theory. Other discussions pertaining to the Borden tracer experiment and subsequent interpretations are given by Sudicky [1988a, 1988b, 1988c], Kemblowski [1988], White [1988], Molz and Güven [1988], Naff et al [1988, 1989], Dagan [1989], Zhang and Neuman [1990], Rajaram and Gelhar [1991], Ritzi and Allen‐King [2007], Woodbury and Sudicky [1992], and others.…”
Section: Introductionmentioning
confidence: 99%
“…Further discussion centering on the applicability of stochastic theories to explain the observed tracer behavior can be found in a number of works. Relevant examples include Dagan [1989a, 1989b], Naff et al [1988, 1989], Kemblowski [1988], Sudicky [1988], Barry and Sposito [1990], Rajaram and Gelhar [1991], and Fitts [1996].…”
Section: Introductionmentioning
confidence: 99%
“…As a part of the discussion under points 1 and 2, there have been a number of conjectures about the stratal architecture of the Borden aquifer. Examples include discussions by Dagan [1989a, 1989b], Naff et al [1988, 1989], Woodbury and Sudicky [1991], and Rajaram and Gelhar [1991].…”
Section: Introductionmentioning
confidence: 99%